Generation Gap for Screening and Treatment of Hepatitis C Virus in Saga Prefecture, Japan: An Administrative Database Study of 35,625 Subjects - Isoda, Hiroshi; Oeda, Satoshi; Takamori, Ayako; Sato, Keiko; Okada, Michiaki; Iwane, Shinji; Takahashi, Hirokazu; Anzai, Keizo; Eguchi, Yuichiro; Fujimoto, Kazuma (Internal Medicine, 2020)
Objective Despite recent advances in hepatitis C virus (HCV) treatment, some HCV-positive individuals are unaware of their infection. The present study aimed to assess the rate and age distribution in Saga Prefecture regarding i) HCV infection and HCV screening and ii) direct acting anti-viral (DAA) treatment. Methods HCV screening data collected at a medical institution or in the workplace were obtained from the administrative database in Saga Prefecture between April 1, 2008 and March 31, 2014. DAA treatment data from Saga Prefecture were obtained from the DAA treatment reimbursement recipient database between October 2014 and March 2017. Results There were 35,625 individuals who underwent HCV screening, and the HCV positive rate was 1.18% (421 individuals), which increased in an age-related manner. The screening rate in the screened populations peaked at 45-74 years of age (approximately 6%) and decreased in the younger and older generations. The estimated percentage of DAA treatment peaked at 65-74 years old (65.8%) and significantly decreased inversely with age in the younger generations; only 9.4% of HCV carriers received DAA treatment in the 20- to 34-year age group. The proportion of subjects who received a complete physical examination for DAA treatment was higher in the subjects who were screened at a medical institution than in those screened at the workplace. Conclusion The rate of subjects who underwent HCV screening and DAA treatment was not high, especially in the younger generation, in Saga Prefecture. This group should be targeted for HCV screening and treatment.